2016
DOI: 10.1016/j.mod.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase 6 catalytic subunit (Ppp6c) is indispensable for proper post-implantation embryogenesis

Abstract: Ppp6c, which encodes the catalytic subunit of phosphoprotein phosphatase 6 (PP6), is conserved among eukaryotes from yeast to humans. In mammalian cells, PP6 targets IκBε for degradation, activates DNA-dependent protein kinase to trigger DNA repair, and is reportedly required for normal mitosis. Recently, Ppp6c mutations were identified as candidate drivers of melanoma and skin cancer. Nonetheless, little is known about the physiological role of Ppp6c. To investigate this function in vivo, we established mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
5
16
0
1
Order By: Relevance
“…Ppp6c homozygous null mutations are early embryonic lethal [45], necessitating use of conditional knockout approaches to study the role of PP6 in vivo . Ye et al [46] engineered mice that are homozygous for a LoxP-targeted allele on chromosome 2, which were crossed with Lck-Cre or CD4-Cre mice to drive selective deletion of the gene for PP6 catalytic subunit (PP6c) at early or intermediate stages of thymocyte development, respectively.…”
Section: Effects Of Ppp6c Knockout and Ppp6r1 (Saps1) Knockout On T Cmentioning
confidence: 99%
“…Ppp6c homozygous null mutations are early embryonic lethal [45], necessitating use of conditional knockout approaches to study the role of PP6 in vivo . Ye et al [46] engineered mice that are homozygous for a LoxP-targeted allele on chromosome 2, which were crossed with Lck-Cre or CD4-Cre mice to drive selective deletion of the gene for PP6 catalytic subunit (PP6c) at early or intermediate stages of thymocyte development, respectively.…”
Section: Effects Of Ppp6c Knockout and Ppp6r1 (Saps1) Knockout On T Cmentioning
confidence: 99%
“…Xenopus, mouse, human) three SAPS genes arose from whole-genome duplication and PP6 forms heterotrimers, where the SAPS and catalytic subunits associate with one of three ANKRD subunits composed of helical ankyrin repeats [6][7][8][9][10]. The loss of PP6 is embryonic lethal in mice [11,12] consistent with fundamental and essential cellular functions. The variety of PP6 functions (see review [3]) and dependence on individual SAPS support the idea that SAPS serve to determine substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PPP6C homozygous null mutations are early embryonic lethal in mice (Ogoh et al, 2016 ). To investigate the functions of PPP6C in vivo , we crossed the Ppp6c f / f mice with Vav1-Cre mice to obtain Ppp6c hematopoietic-specific knockout strain ( Ppp6c f / f : Vav1-Cre ).…”
Section: Resultsmentioning
confidence: 99%